2000
DOI: 10.1093/molehr/6.6.535
|View full text |Cite
|
Sign up to set email alerts
|

HLA-G expression in extravillous trophoblasts is an intrinsic property of cell differentiation: a lesson learned from ectopic pregnancies

Abstract: Human leukocyte antigen (HLA)-G is a major histocompatibility gene expressed almost exclusively in extravillous trophoblasts at the fetal-maternal interface. HLA-G may play a role in protecting the fetus from attack by the maternal natural killer cells. The extravillous trophoblasts invade the decidua and maternal spiral arteries. The factors which regulate the cell-specific expression of HLA-G are unknown. In this study we asked if HLA-G is expressed in extravillous trophoblasts that develop outside of their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(42 citation statements)
references
References 38 publications
0
42
0
Order By: Relevance
“…hPL is also expressed by trophoblasts, with the exception of cytotropholasts,21 and is responsible for the growth and development of the foetus during gestation 33. Likewise CK7 is a keratin filament type expressed in all trophoblast subpopulations,23 34 and HLA-G is a major histocompatibility gene expressed in the placenta throughout the three trimesters of pregnancy by trophoblast lineages 24…”
Section: Discussionmentioning
confidence: 99%
“…hPL is also expressed by trophoblasts, with the exception of cytotropholasts,21 and is responsible for the growth and development of the foetus during gestation 33. Likewise CK7 is a keratin filament type expressed in all trophoblast subpopulations,23 34 and HLA-G is a major histocompatibility gene expressed in the placenta throughout the three trimesters of pregnancy by trophoblast lineages 24…”
Section: Discussionmentioning
confidence: 99%
“…Besides its selective physiologic placental localization, HLA-G has been found in HLA class I positive cells, such as thymic epithelial cells (Crisa et al, 1997), cytokine-activated monocytes (Moreau et al, 1999), and in some pathologic situations, such as pregnancy disorders (Goldman-Wohl et al, 2000), viral infections (Onno et al, 2000), transplantation (Lila et al, 2000), and tumors (Fukushima et al, 1998;Pangault et al, 2002). During the last few years several studies demonstrated that HLA-G molecules were only expressed in a few tumor cell lines (Pangault et al, 1999;Real et al, 1999;Frumento et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a reduced placental IL-10 production was observed in preeclampsia [54] and correlates with a low level of expression of HLA-G transcription [38,55]. On the other hand, the IL-10 homolog produced by cytomegalovirus (CMV) can up-regulate HLA-G protein expression at the monocyte cell surface and is supposed to participate in the mechanisms of escape of CMV to the immune system [56].…”
Section: Cytokines Growth Factors and Hormonesmentioning
confidence: 99%